Self-Awareness Management and Student Learning Understanding Case Study in Politeknik Negeri Sriwijaya - Napitupulu, Rizal Afif Abdullah; Minarni, Ani (ANFUSINA: Journal of Psychology, 2023)
Emotional intelligence has become an important part of achieving learning outcomes and has been proven by previous research. Self-awareness is part of emotional intelligence. Self-awareness student must be managed because it will contribute to the understanding of the student learning outcomes. So students can compete in facing a dynamic environment. This research study was to collect data and insights about student learning outcomes based on the level of self-awareness. The hypothesis of this study is that students who achieve good learning outcomes are students who have good self-awareness and have a positive influence on student learning outcomes. The research sample consisted of 30 students of Sriwijaya State Polytechnic, Bukit class and 11 students of Sriwijaya State Polytechnic, Banyuasin Class. Self-awareness and student learning outcomes were measured by a questionnaire with a Lickert scale. Then, the data were analyzed through SPSS software. The result is that self-awareness has a significant influence on student learning outcomes.